Assessment and selection of vendor in a manufacturing organisation – a graph theoretic approach. Issue 4 (1st January 2013) - Singh, Mohit; Khan, I.A.; Grover, Sandeep
Graph theoretic approach has been adopted for evaluation and selection of vendor. The authors identified five factors affecting the vendor's quality on the basis of 57 research papers of vendor selection and also mentioned the factors chosen by different researchers. On the basis of these factors, a model has been developed for vendor selection. The authors also considered 37 research papers on graph theoretic methodology and mentioned the factors used by different researchers. During the application of graph theoretic approach, a digraph of characteristics which contributes to quality of vendor has been developed further the interdependency of attributes as well as their inheritances has been identified and its representation in matrix form has been used for calculation of numerical index of the vendor's quality through variable permanent function. A single numerical index has been developed graph theoretic approach for assessment and comparison of vendor in manufacturing organisation.